Determinación de los criterios de valoración de marca ciudad como activo intangible aplicado a la marca Quindío (2014)
Intangible assets represent a value very meaning in relation to the total physical, financial etc. These assets represent possible factors of success in the medium and long term, therefore becomes important to know in depth all the benefits that they bring to organizations because "once you really understand the intangibles, you'll never run a business in the same way." (Alvarez, 2010 p.41.) Today, not only public and private entities strive to recognize the intangibles that has now cities understand the essence, customs, and idiosyncrasies can be represented in a new concept called "city brand". The town mark is used as a mechanism to increase the competitive advantage of the territories through new branding strategies to promote culture, identity, landscape and sights of a region are formulated.